FGF23 Producing Mesenchymal Tumor - Lucyna Papierska; Jarosław B. Ćwikła; Waldemar Misiorowski; Michał Rabijewski; Krzysztof Sikora; Hubert Wanyura (Case Reports in Endocrinology)
A 40-year-old patient was referred to Clinic of Endocrinology due to hypophosphatemia causing pain, cramps, and weakness of muscles. Moreover, his bone mineral density was very low. The previous treatment with phosphorus and active vitamin D metabolites was ineffective. In lab tests the hypophosphatemia, hyperphosphaturia, and elevated FGF23 levels were found. Somatostatin receptor scintigraphy (SRS) showed increased radiotracer uptake in the right maxillary sinus and CT scans confirmed presence of tumor in this localization. Biopsy and cytological examination created suspicion of mesenchymal tumor—glomangiopericytoma. Waiting for surgery the patient was treated with long acting Somatostatine analogue, and directly before operation short acting Octreotide and intravenous phosphorus were used. Histology confirmed the cytological diagnosis and the phosphatemia return to normal values in 10 days after the tumor removal.